Optimizing Hand Eye Coordination on Smash Accuracy in Volleyball Extracurricular STKIP PGRI Lubuklinggau - Helvi Darsi; Muhammad Supriyadi; Erick Salman (Sinar Sport Journal, 2021)
The problem in this study is how much influence eye-hand coordination has on the accuracy of the smash of volleyball players at STKIP PGRI Lubuklinggau. Seeing these problems, this study aims to reveal the effect of eye-hand coordination on the smash accuracy of STKIP PGRI Lubuklinggau Volleyball players. This research is an experimental research. The population of this study were students who participated in the volleyball extracurricular of STKIP PGRI Lubuklinggau with 48 members consisting of 25 old players and 23 new players. The sample in this study amounted to 30 male players, which were taken using purposive sampling technique. The research instrumentation used a repeated volleyball test. The data analysis technique used to test the hypothesis in this study is to use the t test formula. The results showed that tcount = 5.017 > ttable 1.699, meaning that hand-eye coordination significantly increased the accuracy of volleyball smashes. Thus, the hypothesis stated earlier can be accepted. Based on the results of the study, it can be concluded that hand-eye coordination has a significant or significant effect on the accuracy of volleyball smash players.